ESTRATÉGIAS DE POLINIZAÇÃO EM ÁREAS URBANAS DE CAMPO GRANDE, MS - JUNIOR, Thomas Roberto dos Santos; FIGUEIREDO, Nataly Sevalio; MOREIRA, Suzana Neves; HOLSBACK, Zildamara dos Reis (ANAIS DO ENIC, 2025)
-